If I Only Had Three Eyes! Jewish Perspectives on Genetic Enhancement - Crane, Jonathan K. (Studia Bioethica, 2017)
Nearly 60 years ago, the Institute of Personality Assessment and Research at the University of California at Berkeley, brought together forty of the most prominent architects in the world to ask them this question: “If man had developed a third arm, where might this arm be attached?” These esteemed professionals debated this provocative idea for nearly an hour. One advocated that it should come out of the top of the head, while another insisted “I think it ought to come right between his shoulder blades, so he can scratch his bottom or his head at will.”